Knowledge exchange enhances engagement in ecological restoration and rehabilitation initiatives. Issue 2 (28th October 2021) - Favretto, Nicola; Stringer, Lindsay C.; Dougill, Andrew J.; Kruger, Liezl
Abstract : Effective knowledge sharing and community engagement can be major enablers in the pursuit of socially relevant benefits from ecological restoration and rehabilitation. Focusing on two ecological restoration and rehabilitation practitioner organizations and their workers, this paper evaluates perceptions of the extent to which short‐term knowledge exchange contributes to social goals in ecological restoration and rehabilitation in South Africa through (1) stakeholder engagement and awareness of community well‐being, and (2) knowledge enrichment. Data collected through impact questionnaires, participatory site visits, practical work exchange, focus group discussions, and a workshop are analyzed using thematic analysis framed by the International Principles and Standards for the Practice of Ecological Restoration #1 and #2. We explore participants' perceptions of knowledge exchange benefits and discuss implications for future collaboration in establishing long‐term knowledge exchange. Findings show that knowledge exchange is perceived to result in enhanced teamwork engagement, and strengthened knowledge on restoration techniques through mutual learning, inspiration, and a strengthened sense of community. Findings suggest that sustained knowledge exchange and engagement activities between different practitioner organizations is key to realize and transform short‐term perceived benefits into long‐term applied socioecological impacts across landscapes in dryland Africa. There is a need to progress from short‐term, horizontal learning, to long‐term (horizontal and vertical) knowledge exchange, to inform restoration project design and implementation.